2021
DOI: 10.3389/fpls.2021.755733
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces Strains Promote Plant Growth and Induce Resistance Against Fusarium verticillioides via Transient Regulation of Auxin Signaling and Archetypal Defense Pathways in Maize Plants

Abstract: Graphical AbstractStreptomyces strains promote plant growth and induce resistance against Fusarium verticillioides via transient regulation of auxin signaling and archetypal defense pathways in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It is, therefore, possible that the strain also produces metabolites able to modulate the plant response when facing the fungus. This phenomenon has already been demonstrated in the interaction of streptomycetes on maize infected by Fusarium verticillioides [32]. The complexity of the interactions occurring between streptomycetes and wheat plant is likely multivariate [30].…”
Section: Discussionmentioning
confidence: 73%
“…It is, therefore, possible that the strain also produces metabolites able to modulate the plant response when facing the fungus. This phenomenon has already been demonstrated in the interaction of streptomycetes on maize infected by Fusarium verticillioides [32]. The complexity of the interactions occurring between streptomycetes and wheat plant is likely multivariate [30].…”
Section: Discussionmentioning
confidence: 73%
“…Streptomyces are acknowledged for their production of phytohormones such as ethylene, gibberellic acid, indole-3-acetic acid (IAA), phenylacetic acid, cytokines, and ACC deaminases [ 18 , 40 ]. Several phytohormones perform critical roles in controlling the growth of plant parts at various stages of development [ 63 ]. PGPRs may synthesize phytohormones comparable to those synthesized by plants, which aid in plant development [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auxin has been reported to participate in plant response to pathogen infection, resulting from host auxin physiology or signaling changes by pathogen challenge or pathogen auxin as well as SA resistance repression ( Wang et al, 2007 ; Yuan et al, 2017 ; Tran et al, 2021 ). Recently, several studies have reported that auxin receptor TIR1 regulates plant immunity ( Su et al, 2021 ), but underlying molecular mechanisms of TIR1 associated with plant response to pathogens remains mysterious.…”
Section: Discussionmentioning
confidence: 99%